Lifetime Earnings and the Vietnam Era Draft Lottery: Evidence from Social Security Administrative Records: Errata - Angrist, Joshua D. (American Economic Review, 1990)
The randomly assigned risk of induction generated by the draft lottery is used to construct estimates of the effect of veteran status on civilian earnings. These estimates are not biased by the fact that certain types of men are more likely than others to service in the military. Social Security administrative records indicate that, in the early 1980s, long after their service in Vietnam had ended, the earnings of white veterans were approximately 15 percent less than the earnings of comparable nonveterans. Copyright 1990 by American Economic Association.